Correction to: The Inconspicuous God: Heidegger, French Phenomenology, & the Theological Turn, by Jason W. Alvis (Literature and theology, 2024)
This is a correction to review: Daniel Boscaljon, The Inconspicuous God: Heidegger, French Phenomenology, & the Theological Turn. By Jason W. Alvis, Li